To the freemen and freeholders, of the city and county of New-York : Friends and fellow-citizens, When I consider the many arduous, expensive, and perilous, struggles that you have made . - Remembrancer (LLMC-digital (Series), 1775)
Advising against choosing loyalists, who have no regard for civil or religious liberties, to defend municipal privileges.